Selection of visual stimuli for the Implicit Association Test for the Obsessive-Compulsive Disorder (IAT-OCD) (Archives of Clinical Psychiatry, 2011)
INTRODUCTION: The identification of cognitive bias in Obsessive-Compulsive Disorder (OCD) remains inconclusive. An area of potential interest includes the examination of visual processing and implicit memory performance. OBJECTIVES: Select visual stimuli to include in a version of the Implicit Association Test (IAT) for OCD. METHODS: Seventeen patients with OCD and 17 healthy controls evaluated 12 visual stimuli related to different dimensions of obsessive-compulsive symptoms and classified the stimuli according to two criteria: "type of impact" (i.e., positive, negative or neutral) and "degree of impact" [i.e., 1 (low impact) to 5 (high impact)]. The chi-square and the Mann-Whitney tests were employed and the level of significance at 0.05. RESULTS: OCD patients evaluated 9 out of the 12 stimuli different from healthy controls in at least one of the two criteria. DISCUSSION: The finding that the figures employed were able to differentiate OCD patients from healthy controls suggests their inclusion in the psychopathological assessment development tools, such as the IAT-OCD.